2018
DOI: 10.1002/art.40569
|View full text |Cite
|
Sign up to set email alerts
|

JAK/STAT Blockade Alters Synovial Bioenergetics, Mitochondrial Function, and Proinflammatory Mediators in Rheumatoid Arthritis

Abstract: This study demonstrates that JAK/STAT signaling mediates the complex interplay between inflammation and cellular metabolism in RA pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
88
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 54 publications
8
88
1
Order By: Relevance
“…Conventional disease-modifying antirheumatic drugs (DMARDs) for RA and psoriatic arthritis (PsA), including methotrexate, leflunomide and apremilast, are anti-metabolic, where they target purine or pyrimidine nucleotide metabolism, the effects of which are known to inhibit both T cells and synovial fibroblast proliferation. Tofacitinib, a JAK1 and JAK3 inhibitor, reduces glycolysis in activated synovial fibroblasts, and in RA synovial explants inhibits key glycolytic enzymes, paralleled by reduced expression of key proinflammatory mediators and synovial fibroblast outgrowths [95]. Tocilizumab, an anti-IL-6 receptor antibody, improved endothelial function and inhibited oxidative stress in RA leucocytes [94].…”
Section: Targeting Metabolism In Rheumatoid Arthritismentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional disease-modifying antirheumatic drugs (DMARDs) for RA and psoriatic arthritis (PsA), including methotrexate, leflunomide and apremilast, are anti-metabolic, where they target purine or pyrimidine nucleotide metabolism, the effects of which are known to inhibit both T cells and synovial fibroblast proliferation. Tofacitinib, a JAK1 and JAK3 inhibitor, reduces glycolysis in activated synovial fibroblasts, and in RA synovial explants inhibits key glycolytic enzymes, paralleled by reduced expression of key proinflammatory mediators and synovial fibroblast outgrowths [95]. Tocilizumab, an anti-IL-6 receptor antibody, improved endothelial function and inhibited oxidative stress in RA leucocytes [94].…”
Section: Targeting Metabolism In Rheumatoid Arthritismentioning
confidence: 99%
“…Tocilizumab, an anti-IL-6 receptor antibody, improved endothelial function and inhibited oxidative stress in RA leucocytes [94]. Tofacitinib, a JAK1 and JAK3 inhibitor, reduces glycolysis in activated synovial fibroblasts, and in RA synovial explants inhibits key glycolytic enzymes, paralleled by reduced expression of key proinflammatory mediators and synovial fibroblast outgrowths [95]. Indeed, interaction of STAT-3 and PKM2 leads to activation of HIF1α, with subsequent induction of cellular invasive mechanisms creating a vicious PKM2/ STAT-3/HIF1 feedback loop [96].…”
Section: Targeting Metabolism In Rheumatoid Arthritismentioning
confidence: 99%
“…In previous studies, the levels of serum cytokine TNF-α and IL-1β are increased in RA patients. Meanwhile, activation of the JAK2-STAT3 pathway is regulated by in ammatory cytokines stimulation during the progression of RA [95,96]. The MAPK family includes p38MAPK, extracellular signal-regulated kinase (ERK) and c-Jun N-terminal kinase (JNK), which were activated in the synovium of RA patients [97,98].…”
Section: Discussionmentioning
confidence: 99%
“…A clinical study concluded that the level of soluble VCAM‐1 emerged as a strong and independent predictor of the risk of hip and knee joint replacement due to severe OA . Another study demonstrated VCAM‐1 is highly expressed in RA whole‐tissue synovial explants . To the best of our knowledge, few previous studies have demonstrated the protective effects of ICAM‐1 and VCAM‐1 in bone disease.…”
Section: Discussionmentioning
confidence: 99%
“…43 Another study demonstrated VCAM-1 is highly expressed in RA whole-tissue synovial explants. 44 To Interestingly, Ren et al reported that when mesenchymal stromal cells (MSCs) were cocultured with activated T cells, they significantly upregulated the adhesive capability of T cells. 45 Moreover, the greater the expression of ICAM-1 and VCAM-1 by MSCs is associated with the greater the immunosuppressive effects exhibited by MSCs.…”
Section: Discussionmentioning
confidence: 99%